Study on the changes of CT texture parameters before and after HCC treatment in the efficacy evaluation and survival predication of patients with HCC - Zhou, Wei; Lv, Yinzhang; Hu, Xuemei; Luo, Yan; Li, Jiali; Zhu, Haidan; Hai, Yucheng (Frontiers in Oncology, 2022)
Objective: To investigate texture parameters of contrast-enhanced CT images before and after transarterial chemoembolization (TACE) as a tool for assessing the therapeutic response and survival predication in hepatocellular carcinoma (HCC). Materials and Methods: Data of 77 HCC patients who underwent three-phase dynamic contrast-enhanced CT examination within 4 weeks before and 4–8 weeks after TACE were collected and efficacy evaluation was performed according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST) standard. The remission group consisted of 31 patients, while the non-remission group consisted of 46 patients. Full-volume manual delineation of the region of interest (ROI) and texture analysis of the ROI were performed on the CT images. Changes in the 48 texture parameters from three-phase CT images before and after TACE were calculated and compared between the two groups. The receiver operating characteristic (ROC) curve and the areas under the curve (AUC) were used to analyze the diagnostic performance of texture parameters. A multifactorial Cox model was used for predicting survival. The C-indices of texture parameter difference values with predictive value and texture features combined with mRECIST in predicting OS were compared with those of mRECIST. Results: 41 changes in texture parameters were statistically significant between the remission and non-remission groups. The ROC curve showed that the AUC of changes in the 90th percentile in the arterial phase was the largest at 0.842. Three changes in texture parameters were independent factors associated with patient survival, with a hazard of 0.173, 2.068, and 1.940, respectively. The C-indices of skewness in the portal venous phase combined with mRECIST (0.729, p=0.015), skewness in the delayed phase combined with mRECIST (0.715, p=0.044), and skewness in both two phases combined with mRECIST (0.728, p=0.017) were statistically different from that of the mRECIST (0.668). Conclusion: Changes in the texture parameters of CT images before and after TACE treatment can be used to obtain relevant grayscale histogram parameters for evaluating the early efficacy of TACE in HCC treatment. And the texture analysis combined with mRECIST may be superior to the mRECIST alone in predicting survival in HCC after TACE treatment.